A guide to maximizing the therapeutic potential of protein–polymer conjugates by rational design. (16th November 2018) - Ko, Jeong Hoon; Maynard, Heather D.
Abstract : Careful planning in the selection of the protein, polymer, conjugation chemistry, and analysis can help maximize the potential of protein–polymer conjugates for therapeutic applications. Abstract : Proteins are an important class of therapeutics that have advantages including high target specificity, but challenges to their use include rapid clearance and low physical stability. Conjugation of synthetic polymers is an effective approach to address the drawbacks and enhance other properties such as solubility. In this review, we present various considerations in synthesizing protein–polymer conjugates for therapeutic applications with a focus on the choice of polymer, protein, and conjugation method, as well as characterization and evaluation of the resulting conjugate in order to maximize the therapeutic potential of the protein drug.